2020
DOI: 10.1007/s40519-020-00988-3
|View full text |Cite
|
Sign up to set email alerts
|

The psychological impact of COVID-19 pandemic on patients included in a bariatric surgery program

Abstract: Purpose The COVID-19 pandemic has radically impacted the world lifestyle. Epidemics are well-known to cause mental distress, and patients with a current or past history of obesity are at increased risk for the common presence of psychological comorbidities. This study investigates the psychological impact of the current pandemic in patients participating in a bariatric surgery program. Methods Patients were consecutively enrolled during the Italian lockdown among those waiting for bariatric surgery or attendin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 48 publications
4
37
2
2
Order By: Relevance
“…Moreover, our results of a decrease in anxiety with no changes in depression scores during the lockdown are in contrast with other data reported in the limited literature available, reporting a significant increase of both anxiety and depression in patients included in a bariatric surgery program [ 9 , 20 , 21 ] and patients with obesity [ 22 , 23 ]). It is to be considered that in these studies, a mixed cohort of patients waiting for different types of procedures were analyzed and the largest sample was represented by post-surgical patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, our results of a decrease in anxiety with no changes in depression scores during the lockdown are in contrast with other data reported in the limited literature available, reporting a significant increase of both anxiety and depression in patients included in a bariatric surgery program [ 9 , 20 , 21 ] and patients with obesity [ 22 , 23 ]). It is to be considered that in these studies, a mixed cohort of patients waiting for different types of procedures were analyzed and the largest sample was represented by post-surgical patients.…”
Section: Discussioncontrasting
confidence: 99%
“…A study investigating the impact of COVID-19 on patients included in a bariatric surgery program (i.e., waiting for bariatric surgery or attending a post-bariatric follow-up) showed that those individuals perceived an increased level of psychological distress along with a worsening of the eating behaviors (15). Accordingly, the majority of our sample reported eating more during the COVID-19 emergency.…”
Section: Discussionmentioning
confidence: 74%
“…In Brazil, one study showed that almost 90% of postbariatric patients were not consuming enough protein and that almost a quarter of their diet consisted of ultraprocessed foods, [38] while another study from Brazil reported that adherence to social distancing orders significantly increased sedentary behaviors and decreased time spent in moderate to vigorous physical activities [39]. Among 434 BS subjects in Italy, who were either waiting for BS or who had completed it, 37% and 56% felt lonelier and more bored, respectively, 66% were hungrier with increased frequency of snacking (55%), 39% reported more impulse to eat, and 49% reported they were unable to follow a recommended diet [40]. While survey studies in adults across the USA and Europe have shown that alcohol consumption has increased during the SARS-CoV-2 pandemic, little is known about the pandemic's effect on substance abuse in patients with prior BS [41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 97%